PROBLEMATIKA PERLINDUNGAN HAK CIPTA DI INDONESIA - Mashdurohatun, Anis (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractDevelopment of copyrighted works as part of the intellectual property rights that stem from results of human creation gave birth to a right of the creator of the so-called copyright. Copyright inherent in the creator differs from other intellectual property rights, because the inherent consists of two types of rights, moral rights and economic rights. The problems of copyright protection in Indonesia is caused by several things including: Islamic view of Copyrights, the public's view of the Copyright, Still Lack Popularizing Copyright Act, the Purchaser is not in the questioning, and legal awareness.